2002
DOI: 10.1016/s0896-6273(02)00912-1
|View full text |Cite
|
Sign up to set email alerts
|

Isomerization and Oxidation of Vitamin A in Cone-Dominant Retinas

Abstract: The first step toward light perception is 11-cis to all-trans photoisomerization of the retinaldehyde chromophore in a rod or cone opsin-pigment molecule. Light sensitivity of the opsin pigment is restored through a multistep pathway called the visual cycle, which effects all-trans to 11-cis re-isomerization of the retinoid chromophore. The maximum throughput of the known visual cycle, however, is too slow to explain sustained photosensitivity in bright light. Here, we demonstrate three novel enzymatic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
170
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 328 publications
(179 citation statements)
references
References 59 publications
(67 reference statements)
9
170
0
Order By: Relevance
“…It was also reported that chicken eyecups contain lower levels of all-trans-retinyl ester but higher levels of 11-cis-retinyl esters than that in mammalian eyes (12,26). The higher isomerohydrolase activity in the chicken RPE could also be responsible for the lower level of all-trans-retinyl esters in the chicken RPE, because all-trans-retinyl esters are more efficiently converted to 11-cis-retinol, which is consequently esterified to 11-cis-retinyl esters for storage (12,26).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…It was also reported that chicken eyecups contain lower levels of all-trans-retinyl ester but higher levels of 11-cis-retinyl esters than that in mammalian eyes (12,26). The higher isomerohydrolase activity in the chicken RPE could also be responsible for the lower level of all-trans-retinyl esters in the chicken RPE, because all-trans-retinyl esters are more efficiently converted to 11-cis-retinol, which is consequently esterified to 11-cis-retinyl esters for storage (12,26).…”
Section: Discussionmentioning
confidence: 95%
“…The chicken retina contains ϳ60% cones, whereas human and bovine retinas have ϳ5% cones (12). Physiological measurements have shown that cones have much faster photoresponse kinetics than rods (9,10).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations